Impact on Soil Physical Properties Related to a High Mechanization Level in the Row Thinning of a Korean Pine Stand - Kigwang Baek; Eunjai Lee; Hyungtae Choi; Minjae Cho; Yunsung Choi; Sangkyun Han (Land, 2022)
In ground-based harvesting, machine traffic can cause soil physical disturbances including excessive compaction, the displacement of the soil surface and topsoil, and rutting. These impacts can indirectly hamper seedling survival and tree growth because of reduced soil permeability and root growth. However, the extent of soil disturbance in mechanized row thinning by harvester and forwarder systems in South Korea is unclear. Therefore, our objectives were to determine the impacts of two types of harvesters, soil textures, and extraction methods on soil compaction and rutting in a Korean Pine stand. The results showed that the machine passes affected soil disturbances. The soil bulk density inside the tracks (at 0–10 and 10–20 cm soil depths) after harvester passes (wheeled vs. tracked) increased by 17 and 27% and 30 and 20%, respectively. The largest impact was recorded for the forwarding track and significant differences were observed between the track and reference locations. Furthermore, the rutting depth in the forwarding trails was significantly higher than in the harvester trails. Thus, the application of a brush mat on harvester and forwarder trails may reduce machine-induced soil compaction. These results provide useful information to help forest engineers and field managers design environmentally sound ground-based harvesting operations.